2018
DOI: 10.1103/physreva.98.013402
|View full text |Cite
|
Sign up to set email alerts
|

Producing long-lived 23S positronium via 33P laser excitation in magnetic and electric

Abstract: Producing positronium (Ps) in the metastable 2 3 S state is of interest for various applications in fundamental physics. We report here on an experiment in which Ps atoms are produced in this long-lived state by spontaneous radiative decay of Ps excited to the 3 3 P level manifold. The Ps cloud excitation is obtained with a UV laser pulse in an experimental vacuum chamber in presence of guiding magnetic field of 25 mT and an average electric field of 300 V cm −1 . The evidence of the 2 3 S state production is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…2 3 S Ps sources have been demonstrated via RF transition from laser-excited 2 3 P Ps in a weak magnetic field [14], via two-photon Doppler-free 1 3 S-2 3 S laser excitation [15,16] and more recently via single-photon excitation of 1 3 S to 2 3 P in a rapidly switching electric field [17] and via single-photon excitation of 1 3 S to 3 3 P with radiative decay to 2 3 S in an electric field [18] and in absence of electric field [19]. This last method in particular showed that it is possible to build an almost-monochromatic 2 3 S Ps source with a selected and tunable velocity distribution in the 10 4 m s −1 range, with an overall efficiency between 0.7 − 1.4% according to the selected velocity [19].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 3 S Ps sources have been demonstrated via RF transition from laser-excited 2 3 P Ps in a weak magnetic field [14], via two-photon Doppler-free 1 3 S-2 3 S laser excitation [15,16] and more recently via single-photon excitation of 1 3 S to 2 3 P in a rapidly switching electric field [17] and via single-photon excitation of 1 3 S to 3 3 P with radiative decay to 2 3 S in an electric field [18] and in absence of electric field [19]. This last method in particular showed that it is possible to build an almost-monochromatic 2 3 S Ps source with a selected and tunable velocity distribution in the 10 4 m s −1 range, with an overall efficiency between 0.7 − 1.4% according to the selected velocity [19].…”
mentioning
confidence: 99%
“…In the present work, following this experimental line, we investigate the possibility of stimulating the 3 3 P-2 3 S transition to increase the overall 2 3 S production efficiency. Indeed, laser-excited 3 3 P Ps can spontaneously decay radiatively to 2 3 S via the dipole-allowed 3 3 P-2 3 S transition (rate A 23 = 2π×1.1·10 7 s −1 ) with ∼10% measured branching efficiency [18,19], limited by the competition with the more efficient spontaneous decay channel 3 3 P-1 3 S (A 13 = 2π × 8.4 · 10 7 s −1 ). Increasing the 3 3 P-2 3 S transition rate, and thus the branching efficiency of the 2 3 S decay, is possible through stimulated emission.…”
mentioning
confidence: 99%
See 3 more Smart Citations